Change in vegetation cover and land use by agricultural activities in the municipality of Bahía de Banderas, Nayarit, Mexico - Bravo Olivas, Myrna Leticia; Morales Hérnandez, Julio César; Gallardo Arce, Bianca Georgina; Carrillo González, Fatima Maciel; Frausto, Oscar (Acta Universitaria, 2022)
Urban growth is considered the main problem causing the transformation of ecosystems, mainly when their transition goes from rural to urban, and it is associated with urbanization processes, population growth, and inefficient development models. The world's vegetation cover has changed due to natural and anthropogenic causes. In Bahía de Banderas, Nayarit, Mexico, these changes are related to the abandonment of agricultural areas. The objective of the research was to identify changes in vegetation cover and land use associated with agricultural activities. For this analysis, the classification of land use during the period 2000-2020 was obtained; this was estimated with the help of three Landsat satellite images processed with geographical information system (GIS) tools, where five vegetation covers were obtained. The results identify accelerated transformations, substituting natural elements for artificial ones; resulting in a lack of balance and integration with the environment, along with built landscapes where different agrarian and rural scenarios have been presented with drastic transformations derived from accelerated urbanization. These effects were caused by the growth of the municipality due to the demand of the tourist sector.